TRANSFORMATION OF THE SOURCE IDEA INTO A FINISHED PRODUCTOF ADAPTIVE FOOTWEAR - KUZINA, NATALIA; LAPCHAK, SVITLANA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article explores a conceptual approach to the creation of adaptive footwear. The main focus is on the methods of transforming inspiration into product design, particularly reconstructive, symbolic, bionic, and modular approaches. Key stages of development are considered, including user needs research, concept development, material selection, prototyping, testing, and manufacturing. The study examines how the use of recycled materials, carrying their own history, combined with thoughtful design solutions, allows for the creation of functional and aesthetically appealing adaptive footwear to meet the needs of various user categories. The process of creating adaptive footwear is complex and multi-stage, involving the transformation of an initial idea into a physically realized product. As existing practice shows, this process often encounters a number of problems related to the efficiency of transformation, the preservation of conceptual integrity, and the соответствие (correspondence/suitability) of the final product to the needs of the target audience.   A key problem is ensuring an effective transition from an abstract visual concept (mood board) to specific technical solutions and prototyping. Insufficient detail at the sketching and design stages can lead to the loss of key aspects of the initial idea, distortion of the symbolic load, and a decrease in the functionality of the finished footwear. Furthermore, there is the problem of integrating recycled materials into the production process of adaptive footwear. These materials have unique physical properties that must be considered at each stage of transformation to ensure comfort, durability, and aesthetic appeal of the product. Another important problem is preserving the social significance and symbolic potential of the initial idea throughout the entire process of creating footwear. The transformation of the source of inspiration requires careful justification of each design decision and its impact on the perception of the finished product. Thus, the problem statement lies in the research and development of effective methods and approaches to transforming the source of an idea into a finished product of adaptive footwear, which allow for the preservation of conceptual integrity, ensure the integration of modern materials, take into account the needs of the target audience, and realize the intended social and symbolic potential. Solving this problem will contribute to the optimization of the process of creating adaptive footwear and increasing its соответствие (correspondence/suitability) to the stated functional, aesthetic, and social criteria.
Keywords: adaptive footwear; design; transformation of inspiration source; technologies; production; transformative shaping